2019
DOI: 10.1177/0972150919846800
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Relationship Between Government Revenues and Expenditures in a Developing Economy: Evidence from a Non-linear Model

Abstract: Understanding the revenue–expenditure nexus is the core essence of this research in the Pakistani context. This research examines the non-linear relationship between government revenues and government expenditures during 1972–2014. The recently developed non-linear co-integration technique has been used along with the symmetry test. The result shows that the revenues and expenditures have co-integration and provide the evidence in favour of fiscal synchronization hypothesis in the budgetary process. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…The results support the fiscal synchronisation hypothesis for the five regions and the tax spending for the Maluku and Papua regions. These are consistent with several studies conducted by Raza et al (2019), Irandoust (2018), Al-Zeaud (2015, Elyasi & Rahimi (2012), Chiang (2009), andGounder et al (2007). The proof of the fiscal synchronisation hypothesis can guide local governments in making policies related to the financial shortfall.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results support the fiscal synchronisation hypothesis for the five regions and the tax spending for the Maluku and Papua regions. These are consistent with several studies conducted by Raza et al (2019), Irandoust (2018), Al-Zeaud (2015, Elyasi & Rahimi (2012), Chiang (2009), andGounder et al (2007). The proof of the fiscal synchronisation hypothesis can guide local governments in making policies related to the financial shortfall.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have also found the occurrence of the hypothesis in 40 Asian countries from during 1995-2008 (Mehrara et al, 2011), Iran from 1963 to 2007 with ECM (Elyasi & Rahimi, 2012), Jordan from in 1990-2011 with granger causality and VECM (Al-Zeaud, 2015). Furthermore, similar ‹ 37 › results were obtained in Pakistan from during 1972-2014 with the adopted non-linear ARDL method (Raza et al, 2019), Greece from the period 1833 to 2009 with the granger causality test method (Richter & Dimitrios, 2013), and Zambia, during the period 1980-2016 using the VAR method (Champita, 2016), as well as nine industrialised countries from 1953-1992 using the structural VAR model (Koren & Stiassny, 1998).…”
Section: Literature Reviewsupporting
confidence: 56%
“…In general, the findings of this study are in line with the findings of research conducted by Aidam (2018) and Raza et. al.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, Hasan and Kashmir (2016) identified a negative relationship in the short term. Furthermore, the relationship in the long-term of government expenditure and government revenue was also observed in Ghana (Aidam, 2018), and Pakistan (Raza et. al., 2019).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation